Special topics in education, volume 2 - Andas, Celia D.; Parpa, Janet C.;Morales, Kathlee M;Cespon, Laura V;Dorado, Leonardo B ;Pidor, Sylvia J;Lozarita, Marilou T;Cadosales, Maria Nancy Q;Alderite, Thelma O;Daligdig, Romeo M (Cubao, Philippines : Lorimar Publishing Company Inc., 2012)
These modules on Special Topic in Education are PAFTE's response to the need for instructional material for the three-unit professional education course in Special Topics. It is a compilation of at least ten (10) Modules written by members of PAFTE all over the country for PAFTE members most especially and also for non- PAFTE members. The teacher education curriculum includes a three-unit course on Special Topics to give every teacher education institution an opportunity to select current issues and topics not included in the other professional education courses but are seen to be important and highly relevant to its mission vision. The course on Special Topic likewise gives the teacher education student an opportunity to explore topics and issues related to his/ her field of study.
Mother Tongue Based-Multilingual Education/ Janet C. Parpa 1 -- Multicultural Education / Kathleen M. Morales 10 -- Catering to Diverse Learners Through Multi- Grade / Laura V. Cespon 19 -- Graphic Organizers as Thinking Technology / Thelma O. Alderite 32 -- Conflict Resolution: Contextualized Approach to Learning/ Leonardo B. Dorado 45 -- Authentic Assessment: Let's Do It! / Sylvia J. Pidor 53 -- The Art of Questioning / Cecilia D. Andas 61 -- Transformative Education / Marilou T. Lozarita 73 -- Problem - Based Learning: The Pedagogical Adventure / Maria Nancy Q. Cadosales and Romeo M. Daligdig 83 -- Integrative Teaching Strategies / Romeo M. Daligdig 91
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES